Indigenous holistic education in philosophy and practice, with wampum as a case study - Morcom, Lindsay (Foro de Educación, 2020)
Morcom, L. A. (2017). Indigenous holistic education in philosophy and practice, with wampum as a case study. Foro de Educación, 15(23), 121-138. doi: http://dx.doi.org/10.14516/fde.572 This article examines holistic educational philosophy from a North American Indigenous perspective, with a particular focus on Anishinaabe philosophy. Holism intercalates every aspect of Anishinaabe and many other Indigenous epistemologies, including one’s understanding of the self and one’s relationship to the community, other living things, the earth, and the divine. This orientation has a significant impact on pedagogy and classroom practice. It also determines how curriculum is understood and utilized from an Indigenous perspective; in stark contrast to the compartmentalization of subjects in the Western education system, Indigenous educational philosophy focuses on interrelationships between different subjects. This perspective is central to Indigenous sense-making. While the fundamental assertions of Western and Indigenous educational philosophies are significantly different, it is possible to meet Western curriculum expectations through Indigenous pedagogy by enacting holistic teaching practices and focusing on topics and interrelations. A study of classroom teaching focusing on wampum, which is culturally significant to numerous First Nations in the eastern woodlands of North America, offers an excellent example of how teachers may touch on all Western curriculum subjects and meet government mandated curriculum expectations while still teaching holistically in a way that is coherent with Indigenous educational philosophy.